Clinical Spectrum and Diagnosis of Enteric Fever: A Cross-Sectional Study - Amanullah Lail, Bismah Memon, Shahid Latif, Tazeem Hussain, Muhammad Ghazi Asad Khan, Sajid Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Enteric fever is also known as paratyphoid fever or typhoid fever. Approximately 14.3 million cases around the world were due to enteric fever. Typhoid leads to a number of complications as well as mortality. It is a multi-system disease that involves several organs. Objective: To determine the clinical spectrum and diagnosis of enteric fever. Study design: A cross-sectional study Place and Duration: This study was conducted at DMC/DUHS Civil Hospital Karachi from December 2020 to December 2021. Methodology: All of the participants in this research were aged from 18 years to 75 years. All of the participants had clinically suspected cases of enteric fever because they had a fever for more than 3 days. Blood samples were collected from all the patients. On the sample collected, the lgM antibody test, blood culture, Loop-mediated isothermal amplification, and Widal test were conducted. Moreover, every patient’s detailed history, which includes demographics as well as prior medical history, was also obtained. All of the data was gathered using a pre-designed and pre-tested schedule. Results: There were a total of 80 patients involved in this research. There were 44 females and 36 males. The majority of the participants’ ages ranged from 21 years to 30 years. A total of 39 patients were treated as in-patients while 41 patients were treated as out-patients. Most patients had complaints about abdominal pain, headaches, and fever. There were 41 culture-negative patients and 39 culture-positive patients. The mean time period among culture-negative patients was 8.3 days, while it was 8.6 days among culture-positive patients. When blood was obtained between 6 and 10 days of fever, maximum blood culture positivity and maximum Widal positivity were observed. Conclusion: Widal and blood cultures performed better between 6 and 10 days of fever, whereas IgM performed best in the first 5 days of fever. Keywords: Enteric fever, adults, Blood C/S, Widal test